Числове дослідження особливостей мокрої очистки газів у скрубері Вентурі - Fedinchyk I.V. (General Energy Institute of the National Academy of Sciences of Ukraine, 2014)
Improvement of the efficiency of the cleaning of flue gases of coal-fired boilers from ash particles is an important environmental problem. Among apparatus for wet cleaning, Venturi scrubbers are the most efficient, but their characteristics do not meet the present-day requirements, although the possibilities of improvement of their work are far from being exhausted. The most rational way of solution of this problem is connected with mathematical modeling. Such a model has been built, and the program was developed on this basis. With its help, we have performed numerical investigations of the influence of three-phase polydisperse flow parameters as applied to the process of gas cleaning in a Venturi scrubber.On the example of the most characteristic variant of calculations, we have analyzed the laws of change in the velocity of phases and specific flow rate of particles along the flow length. We have studied the dependence of the efficiency of ash catching on water consumption, the initial velocities of drops and gas, and the section of liquid entrance to the scrubber. It has been shown that particle catching becomes better with increase in the scrubber watering, gas velocity, distance between the section of liquid entrance and the scrubber throat as well as with decrease in the drop velocity. We have also explained the dependences obtained.